The Pentynoate Ligand as a Building Block for Multimetallic Systems - Lin, Y; Duclaux, L; de Rivera, F; Thompson, A; Wilton-Ely, J (Wiley, 2014)
The complexes [RuRCl(CO)(BTD)(PPh3)2] (R = CH=CHtBu, CH=CHC6H4Me-4, CH=CHC5H4FeC 5H5; BTD = 2,1,3-benzothiadiazole) and [Ru{C(C≡CPh)=CHPh}(CO)(PPh3)2] reacted with pentynoic acid to yield the same complex, [RuCl(O2CCH 2CH2C≡CH)(CO)(PPh3)2], through cleavage of the vinyl ligand. In contrast, the products [RuR(O 2CCH2CH2C≡CH)(CO)(PPh3) 2] were formed when NaO2CCH2CH 2C≡CH was used. An osmium example, [Os(CH=CHC6H 4Me-4)(O2CCH2CH2C≡CH)(CO) (PPh3)2], was also prepared from treatment of [Os(CH=CHC6H4Me-4)Cl(CO)(BTD)(PPh3) 2] with NaO2CCH2CH2C≡CH. Coupling of the pendant alkyne in [RuCl(O2CCH2CH 2C≡CH)(CO)(PPh3)2] to yield the homodimetallic complex [{RuCl(O2CCH2CH2C≡ C)(CO)(PPh3)2}2] was achieved by using [PdCl2(PPh3)2], CuI and NEt3. The reactivity of the alkyne unit was further exploited by the metallation of the alkyne with ClAu(PR3) (R = Ph, Cy) and Co2(CO)8 to yield the multimetallic species [Ru(CH=CHC6H4Me-4) (O2CCH2CH2C≡CAuPR3)(CO) (PPh3)2] and [Ru(CH=CHC6H4Me-4) (O2CCH2CH2CC{Co2(CO) 6}H)(CO)(PPh3)2]. The structures of the complexes [Ru(CH=CHC6H4Me-4)(O2CCH 2CH2C≡CH)(CO)(PPh3)2] and [Ru(CH=CHtBu)(O2CCH2CH2C≡CH)(CO)(PPh 3)2] were determined crystallographically. Organometallic ruthenium and osmium pentynoate complexes were prepared, and the pendant alkyne functionality was used to form homodimetallic and heteronuclear di- and trimetallic complexes. Copyright © 2014 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.